TELAAH PESAN DAKWAH DALAM FILM TILIK (STUDI ANALISIS SEMIOTIKA) - Mustofa, Muhamad Bisri; Wuryan, Siti; Rahmayeni, Syamzakiah (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2021)
Along with the development of the times and technology, of course there are many things that must be addressed in carrying out da'wah activities so that they are in accordance with the development of today's society. This includes the use of various existing media for da'wah purposes, both in print, internet and electronic media which are considered more effective and efficient in conveying da'wah messages, one of which is film. The focus of the problem to be studied is what are the da'wah messages contained in the film Tilik Karya Wahyu Agung Prasetyo. The purpose of this study was to determine the messages of da'wah contained in the film. This study uses a qualitative method. This type of research is library research. The data were then analyzed using Roland Barthes' Semiotics which emphasized two levels of signification, namely the denotation stage and the connotation stage. The results of this study indicate that the Tilik film contains da'wah messages which include creed, sharia, and morals.